Smart contract for promise of sale - Garnica-Mérida, Jairo Jessiel (DIXI, 2025)
Purpose. Sales require the fulfillment of a solemnity for their perfection, as contemplated in the second literal article 1857 of the Civil Code. In contrast, the promise of sale does require solemnity, although more flexible, as established in the first numeral of article 1611 of the same code, since only literality is required. The latter will be the object of the investigation, since it can be reproduced in a smart contract. It is not only about transcrib- ing a promise on a computer, but it goes further, applying the decentralized system of the Blockchain; which also allows the decentralization of information, thus creating an automatic “Backup” of the metadata that we enter. Methodology: Inductive - Qualitative of Comparative Law. Results. Colombia has great legal potential in technology and innovation, as demonstrated by its regulatory history. For decades, laws such as 270 of 1996 and 527 of 1999 have been fundamental pillars in the construction of a digital Colombia. However, it was not until the arrival of a global pandemic that business, contracts and judicial procedures were allowed to be carried out through new technologies. Even more relevant, this context promoted the creation of new offices and firms oriented towards innovation and technological integration in the country’s daily life. Conclusions. By automating the obligations contained in a promise of sale, we will reduce the risks of possible errors or crimes in the contracts. Likewise, involuntary mistakes that could arise in these agreements are avoided.